Hepatitis B in Africa Collaborative Network: cohort profile and analysis of baseline data. (3rd April 2023) - Riches, Nicholas; Vinikoor, Michael; Guingane, Alice; Johannessen, Asgeir; Lemoine, Maud; Matthews, Philippa; Okeke, Edith; Shimakawa, Yusuke; Sombie, Roger; Stockdale, Alexander; Wandeler, Gilles; Andersson, Monique; et al.
Abstract: Approximately 80 million people live with chronic hepatitis B virus (HBV) infection in the WHO Africa Region. The natural history of HBV infection in this population is poorly characterised, and may differ from patterns observed elsewhere due to differences in prevailing genotypes, environmental exposures, co-infections, and host genetics. Existing research is largely drawn from small, single-centre cohorts, with limited follow-up time. The Hepatitis B in Africa Collaborative Network (HEPSANET) was established in 2022 to harmonise the process of ongoing data collection, analysis, and dissemination from 13 collaborating HBV cohorts in eight African countries. Research priorities for the next 5 years were agreed upon through a modified Delphi survey prior to baseline data analysis being conducted. Baseline data on 4, 173 participants with chronic HBV mono-infection were collected, of whom 38.3% were women and the median age was 34 years (interquartile range 28–42). In total, 81.3% of cases were identified through testing of asymptomatic individuals. HBeAg-positivity was seen in 9.6% of participants. Follow-up of HEPSANET participants will generate evidence to improve the diagnosis and management of HBV in this region.